PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PERAWAT DAN BIDAN DI RUMAH SAKIT IBU DAN ANAK (RSIA) PURI BUNDA DENPASAR - Ni Nyoman Diliyanti; Gde Bayu Surya Parwita; Gede Gama (Forum Manajemen STIMI Handayani Denpasar, 2018)
The purpose of the research is to understand the organization culture ant working satisfaction on the performance of nurse and midwife in RSIA Puri Bunda Denpasar.The data collection technique in this research is observation, interview and questioner with likert measurement. The population of the research is 143 nurses and midwifes where 105 of the respondents are selected as samples. The sampling technique is probability sampling which is proportionate stratified random sampling. The analysis method is double linear regression analysis. The result of the research shows:1) Partially, the culture of the organization has positive and significant effect on the performance of nurses and midwifes. 2) Working satisfaction has positive and significant effect on the performance of nurses and midwifes. 3) Simultaneously, organization culture and working satisfaction has positive and significant effect on the performance of nurses and midwifes in RSIA Puri Bunda Denpasar. There is great hope that there is clear rule and system regarding the organization culture and working satisfaction so the performance of nurses and midwifes in RSIA Puri Bunda Denpasar can be increased. The increasing in performance will lead to better and continuous service given to the society.